Comparative evaluation of antioxidant effects: Green tea versus bamboo salt on the pushout bond strength of bioceramic sealers – An in vitro study - Yasmeen Mohd. Azeem; Kiranmayi Govula; Lavanya Anumula; Punamalli Symon Prasanth; Karthik Nagella; Shilpa Gollaprolu (SRM Journal of Research in Dental Sciences)
Background: Sodium hypochlorite (NaOCl) used for irrigation reduces the bond strength between the sealer and radicular dentin. The aim of this study was to evaluate and compare the efficacy of natural antioxidants on the pushout bond strength (PBS) of bioceramic sealers to root canal dentin. The influence of bioceramic (BC)-impregnated GP was also evaluated. Materials and Methods: Forty single-rooted extracted human teeth were randomly divided into two groups (n = 20): Group 1 (bioceramic sealer + bio-ceramic impregnated GP) and Group 2 (bioceramic sealer + normal GP). The two groups were further divided into three subgroups based on the final rinse used: Group 1a (saline), Group 1b (25% bamboo salt [BS]), Group 1c (green tea [GT] polyphenols), Group 2a (saline), Group 2b (25% BS), and Group 2c (GT polyphenols). PBS testing was done. Results: 3% NaOCl significantly decreased the bond strength of BC sealer to dentin (P < 0.05). Conclusion: Both the antioxidants used and bioceramic-impregnated gutta-percha showed higher PBS.